KINERJA PERAWAT RUMAH SAKIT PERMATA BEKASI DIPENGARUHI OLEH KOMPENSASI MELALUI MOTIVASI KERJA - Hukman Nurriza; Edy Sanusi Silitonga (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2023)
This study aims to analyze the effect of the performance of nurses at Permata Bekasi Hospital on compensation through work motivation. Research using quantitative descriptive analysis method. The number of samples is 66 respondents, determining the sample using random sampling method. In this study the model test that will be carried out is to use path analysis. The results of the intervening test, it shows that the value of the indirect effect of compensation through work motivation on nurse performance is greater than the direct effect of compensation on nurse performance. So this shows that work motivation can be a variable that mediates the influence between compensation and nurse performance.